Análisis de vulnerabilidad y riesgo de incendio en instalaciones administrativas Municipalidad de Belén Loreto 2024 - Castro del Castillo, Carlos Jhonatan Ruben (2025)
The fire risk in the administrative facilities of the Municipality of Belén presents significant concerns due to the lack of adequate preventive measures and the structural vulnerability of the workspaces. The study aims to assess the safety conditions and fire risks in these facilities. To achieve this, deficiencies in both infrastructure and organizational management have been identified. The theoretical framework is based on international studies on fire risk factors, such as the presence of flammable materials, electrical overload, and the lack of detection and extinguishing systems. The applied methodology included a diagnosis based on surveys, data analysis, and the use of the FRAME method to evaluate vulnerability and risk. The results revealed that 50% of the factors evaluated exceed the safety threshold, especially in areas related to the safety of people and fire prevention systems. In conclusion, it is recommended to implement improvements in electrical infrastructure, conduct regular drills, update fire detection systems, and strengthen workplace safety training to ensure a safe environment.